Non-financial risk disclosure: from narratives to an index based on Delphi technique - Adibah Jamil,; Mohamat Sabri Hassan,; Norman Mohd Salleh,; Rubayah Yaakob, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The inconsistency in research findings on the level of non-financial risk disclosure might be due to the measurement applied in prior studies. Prior studies measured non-financial risk disclosure by using manual text analysis. The results only covered types of non-financial risk disclosures that are only being reported in the company’s annual report, which is significant to the shareholders but not for the other stakeholders. However, stakeholders view is important as it will lead to long-term performance. Hence, the present research aims to identify non-financial risk information based on stakeholders’ expert opinions captured through a Delphi technique and ultimately to develop a non-financial risk disclosure index (NFRDI) which will benefit all stakeholders. This index is imperative as it will lead to most significant non-financial risk as it is based on the needs of all stakeholders as compared to excessive information prepared by the researchers. This study uses a sample comprising 313 companies listed in Bursa Malaysia from 2016 to 2018 to investigate level of non-financial risk disclosure among non-financial companies. Following a content analysis, the companies’ annual reports were examined using the NFRDI. Findings show that non-financial risk reporting in Malaysian public-listed companies is still inadequate. However, the disclosure of several non-financial risk items has increased from 2016 to 2018. These results reveal that listed companies need to improve their risk reporting for the benefit of the stakeholders. This study contributes to fill the gap by identifying the risk factors and types of non-financial risks that are relevant to the investors and other stakeholders from the perspectives of experts. The NFRDI crafted is expected to be useful to the regulators and listed companies to enhance a transparent non-financial risk disclosure.